New species of Rhamphomyia (Diptera: Empididae) from Turkey with a key to species of the Middle East and adjacent territories - Barták, Miroslav; Kubík, Štěpán; Civelek, Hasan Sungur; Dursun, Oktay (Zootaxa, 2014)
Rhamphomyia (s. str.) academica sp. nov. (Turkey) and R. (s. str.) soukupi sp. nov. (Turkey) are described and illustrated. Rhamphomyia (Lundstroemiella) cimrmani Barták, 2006, is re-described and the female is newly described. The first records of Rhamphomyia (s. str.) argentata von Röder, 1887 and R. (Pararhamphomyia) intersita Collin, 1960 are reported from Turkey. A key to species of Rhamphomyia from the Middle East is presented.